TPEN, a transition metal chelator, improves myocardial protection during prolonged ischemia - Karck, Matthias; Appelbaum, Y.; Schwalb, Herzl; Haverich, Axel; Chevion, M.; Uretzky, Gideon (The journal of heart and lung transplantation, 1992)
In view of the hypothesis that free radicals induced damage during ischemia and reperfusion is mediated by transition metals, we investigated the effect of the potent metal chelator TPEN (N,N,N'N'-tetrakis(-)[2-pyridylmethyl]-ethylenediamine) on cardiac function after prolonged myocardial ischemia. Isolated working rat hearts were subjected to 12 hours of cold ischemic arrest followed by reperfusion for 1 hour. The study was carried out on five groups (nine hearts in each): (1) St. Thomas' Hospital cardioplegic solution; (2) St. Thomas' Hospital cardioplegic solution with 7.5 mumol/L TPEN; (3) protection conditions as in group 2, but with TPEN administration during preischemic and reperfusion periods; (4) University of Wisconsin solution; and (5) the same conditions as in group 4 with TPEN administration during the preischemic and reperfusion periods. Significant enhancement of hemodynamic recovery was observed in the presence of TPEN throughout the experiment. The recovery of cardiac output was 24% +/- 4% in group 3, as compared to 12% +/- 4% in group 1 (p < 0.01). The postischemic left ventricular pressure recovery was 57% +/- 4% in group 3, as compared to 18% +/- 7% in group 1 (p < 0.005). The hearts in group 5 recovered, reaching 29% +/- 2% of the preischemic cardiac output and at 65% +/- 2% of the left ventricular pressure recovery (p < 0.05 versus group 3). Lactate dehydrogenase was released throughout the reperfusion. TPEN addition to groups 2 and 3 did not significantly reduce lactate dehydrogenase release; however, TPEN in University of Wisconsin solution and throughout the experiment significantly decreased lactate dehydrogenase release.(ABSTRACT TRUNCATED AT 250 WORDS)